The effect of convalescent plasma on the treatment of COVID-19 patients in Ardabil, Iran - Effat Iranijam; Hassan Ghobadi; Somaieh Matin; Shahram Habibzadeh; Hamed Zandian; Jafar Mohammadshahi; Shahnaz Fooladi; Abdollah Dargahi; Elham Safarzadeh; Mohammad Negaresh; Javad Hosseini; Ali Hossein Samadi; et al. (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Infection with COVID-19 has resulted in considerable mortality all around the world. This study aimed to investigate the effect of convalescent plasma on the treatment of hospitalized patients with COVID-19 in Imam Khomeini Hospital at Ardabil, Iran. MATERIALS AND METHODS: In this quasi-experimental clinical trial, patients over 18 years of age with polymerase chain reaction-positive COVID-19 were admitted based on the clinical criteria of respiratory distress with hypoxia (O2 saturation <90) and tachypnea (R Relative Risk (RR) >24) with moderate-to-severe lung involvement and in the 1st week of respiratory disease who were not intubated were nonrandomly assigned to two groups: convalescent plasma therapy (CPT) group (197 cases) and control group (200 cases). We used the Chi-square, t-test, Fisher's exact test, and Pearson's correlation coefficient for statistical analysis. RESULTS: Analyses revealed that length of stay in hospital was significantly lower in the CPT group as compared to the control group (P = 0.001). Twenty-four cases (22.0%) in the CPT group and 85 cases (78.0%) in the control group needed intubation. Furthermore, mortality was 17 cases (18.3%) in the CPT group and 76 cases (81.7%) in the control group, the difference of which was also found to be statistically significant (P < 0.05). CONCLUSIONS: It seems that CPT can be used as an alternative treatment at the early stages of COVID-19 to prevent the progress of the disease, reduce the need for intubation and consequently the length of stay in hospital, and finally, decrease mortality.